마이크로 스케일 물체의 3차원 정보 획득을 위한 구조 조명 현미경 최적화 기술 - 한정헌(Jeong-Heon Han); 강지훈(Ji-Hoon Kang); 주병권(Byeong-Kwon Ju); 김명하(Myung-Ha Kim) (디지털콘텐츠학회논문지, 2019)
최근, 가상현실 기기와 콘텐츠 제작 기술의 발전으로 유명 유적이나 관광지를 3차원 실사로 구현하여 원격으로 체험할 수 있게 되었다. 미시세계를 가상현실로 구현하기 위해서는 실사하는 것이 가장 좋은 방법이다. 본 논문에서는 마이크로 스케일을 갖는 물체의 3차원 정보를 획득하기 위한 구조 조명 현미경 최적화 기술에 대해 다루고자 한다. 구조 조명 현미경 (Structured illumination microscopy, SIM)은 흐려짐을 줄이고 축 해상도를 증가시킬 수 있는 광학 단면 기술을 사용하는 3 차원 측정 방법 중 하나이다. 이때, 최대 단면 강도는 정규화 공간 주파수가 1인 격자 패턴을 사용하여 수행되었으며, 적절한 고공간 주파수 격자 패턴에 의해 광학 단면을 최적화하여 미시세계를 실사화 할 수 있었다. Recently, with the development of virtual reality (VR) devices and contents production technology, it is possible to experience famous historic sites or tourist spots remotely. In order to realize the microscale world as VR, it is the best way to take a picture of objects from the real world. In this paper, we introduce the optimization of structured illumination microscopy (SIM) with a grid pattern of a suitable spatial frequency for acquiring three-dimensional information of a microscale object. SIM is one of three dimensional measurement approaches using optical sectioning technique which can decrease a blurring and increase the axial resolution. The optimal sectioning wsas achieved by using a grid pattern with a normalized spatial frequency of unity, and the microscopic world could be realized by optimizing optical sectioning by a suitable high spatial frequency grid pattern. KCI Citation Count: 0